1997
DOI: 10.1017/s0021859696003942
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing wheat grain yield: effects of Rht (gibberellin-insensitive) dwarfing genes

Abstract: Four sets of near-isogenic lines carrying different combinations of the alleles Rht-B1b, Rht-D1b and Rht-B1c for gibberellin-insensitive dwarfism in hexaploid wheat (Triticum aestivum L.) were compared with tall controls in a series of yield trials in eastern England and central Germany. In all four varietal backgrounds the effects of Rht-B1b and Rht-D1b were similar (plant height ≈ 86 and 83% of tall controls respectively) and in combination reduced plant height to c. 58%. The Rht-B1c allele c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
300
5
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(345 citation statements)
references
References 0 publications
33
300
5
7
Order By: Relevance
“…During the Green Revolution, reduction of plant height was one of the main breeding targets for cereals, leading to an increase in grain yield. However, this process seems to have some physiological limitations, and further reduction of plant height may negatively affect yield potential (Flintham et al 1997;. Therefore, QTL that affect lodging without affecting height can be of great value in further reducing lodging resistance.…”
Section: Lodging Tolerance and Plant Heightmentioning
confidence: 99%
See 1 more Smart Citation
“…During the Green Revolution, reduction of plant height was one of the main breeding targets for cereals, leading to an increase in grain yield. However, this process seems to have some physiological limitations, and further reduction of plant height may negatively affect yield potential (Flintham et al 1997;. Therefore, QTL that affect lodging without affecting height can be of great value in further reducing lodging resistance.…”
Section: Lodging Tolerance and Plant Heightmentioning
confidence: 99%
“…A few dwarfing genes are available in oat that have been successfully used in the last decades by breeders, producing high-yielding varieties with lower lodging risk (Marshall and Murphy 1980;Milach et al 1997;Morikawa et al 2007). However, reducing plant height too much can have a detrimental effect on yield potential (Flintham et al 1997). Knowledge about genetic factors controlling stem strength and root anchorage in cereals and their effect on lodging tolerance is scarce, probably because these are complex traits that may be affected by many factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Because the dwarf and non-dwarf near-isogenic lines are virtually identical for all other genes, the differences between the two lines in the same environment can be attributed to their dwarfing gene differences. For example, Flintham et al (1997) grew semidwarf and dwarf near-isogenic lines of 'Maris Huntsman', 'Maris Widgeon', 'Bersee', and 'April Bearded' wheat in six trials to study the effect of the dwarfing genes. The lines grew to different heights in each environment (e.g., April Bearded, a tall or conventional height cultivar, was 1.30, 1.54, 1.27, 1.50, 1.39 and 1.48 m in Trials 1-6, respectively).…”
Section: Plant Genotype and Plant Phenotypementioning
confidence: 99%
“…A full dwarf line has both Rht-B1b and Rht-D1b in the homozygous condition (e.g., Rht-B1b Rht-B1b and Rht-D1b Rht-D1b). A full dwarf is shorter than either semidwarf but is also shorter than if the effects (in this case the proportional plant height) of the two semidwarf genes were multiplicative (Flintham et al, 1997; Table 1). Hence, the presence of one semidwarfing gene increases the effect of a second semidwarfing gene.…”
Section: Gene Actionmentioning
confidence: 99%
“…Similar results were reported by Min (2001). Flintham et al, (1997) observed that in wheat plant height between 70 cm and 100 cm was best for maximum photosynthetic capacity in a canopy. Though, the plant height was positively correlated with total dry weight, it was negatively correlated with stem strength, chain weight, LRFI, grain yield and harvest index.…”
Section: Resultsmentioning
confidence: 98%